Effects of taurine supplementation on metabolic health and biological aging in healthcare workers: A protocol for a triple-blinded, Bayesian-optimized phase II randomized controlled trial - Mandy H. M. Chu; Jacky K. M. Lai; Anna Lee; William K. K. Wu; Ziheng Huang; Henry M. K. Wong; Laptin Ho; Hao Su; Samantha S. M. Ho; Xinbo Xu; Warren Pavey; David J. R. Morgan; et al. (PLoS ONE, 2026)
Background Metabolic-related diseases become increasingly prevalent with age. Recent experimental evidence suggests that taurine (2-aminoethanesulfonic acid) deficiency contributes to these conditions, despite taurine being classified as a conditionally essential amino acid. Purpose This study aims to assess whether a 6-month oral taurine supplementation program improves blood glucose control and other health parameters among healthcare workers. Methods This study is a Bayesian-optimized phase II 1:1 randomized controlled trial. Participants will be randomly assigned to receive oral taurine (3 g/day) or an indistinguishable placebo for 6 months, stratified by (a) diabetes mellitus status and (b) age > 45 years. Assuming non-informative priors , posterior probabilities of effectiveness in reducing glycated hemoglobin (HbA1c) will be evaluated after enrollment of 20, 40, and 60 participants, if outcome data are available at those timepoints, to determine whether the trial should be stopped early for futility or superiority, prior to the planned total enrollment of 80 participants (protocol 1.4 on 19 th September 2025). Outcomes The primary outcome is the proportion of participants achieving any reduction in HbA1c at 6 months compared with baseline. Secondary outcomes include changes in plasma lipid levels, blood pressure, PhenoAge, body weight, and skin autofluorescence index. Discussion This phase II trial applies a Bayesian-optimized design to evaluate the potential health benefits of oral taurine supplementation. The findings will inform whether a sufficiently powered phase III randomized controlled trial is warranted to define the role of taurine in promoting metabolic health. Trial registration This trial is registered with the Chinese Clinical Trial registry ( https://www.chictr.org.cn/hvshowprojectEN.html?id=277124&v=1.02025-05-21 ; Identifier: ChiCTR2500102879).